The wimpy kid Do it yourself book - Kinney, Jeff (London: Penguin books, limited (UK), 2011)
Now everyone can have their own Wimpy Kid diary! Draw your own Wimpy-Kid-style cartoons, fill in facts and lists, check out the full-colour comics inside and even write your own Wimpy Kid journal, just like Greg. This title now comes with dozens of pages of new content and a brand new cover.